(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The development of both the banking sector of the country and the entire economy is dependent on the level of capitalization, because its insufficiency hinders economic development. That is why the study of capitalization, as well as finding ways to increase it, is relevant. There are different indicators of determining the level of banking sector’s capitalization, but the main one is the share of banks’ capital in GDP. However, in practice, the dynamics and structure of banks’ capital and the its usage efficiency are often analyzed. The purpose of the article is to analyze the banking system capitalization, to make comparative characteristic with Poland, Switzerland and Germany, as well as to develop theoretical and applied recommendations on the formation of bank capital and increase the Ukrainian banking system capitalization. Results. The level of Ukrainian banking system capitalization was determined on the basis of the share of banks’ capital in GDP for 2000-2019. The decrease in the level of Ukrainian banking system capitalization by the analyzed indicator is caused by several factors: 1) excess of GDP growth rate over the growth rate of bank capital; 2) significant decrease in the number of banks in the banking system of Ukraine and, as a result, a decrease in banking capital. The main share in the banks’ capital structure is the authorized capital, which is formed due to the owners’ funds. Uncovered loss, which reaches more than 100% from 2016 to 2019, has a negative impact on the amount of equity, that is, in the post-crisis period there is an accumulation of uncovered loss in the banking system of Ukraine. Despite the large number of banks in the Ukrainian banking system, 49.96% (half) of the banking system’s capital is accounted for by only 5 banks. Considering the significant changes in the banking system of Ukraine that have come under the pressure of financial crises and as a result of the implementation of international standards of banking regulation, we consider it advisable to perform a comparative analysis of the capitalization of the banking systems of Ukraine, Poland, Switzerland and Germany. We can say that the National Bank of Ukraine should consider the experience of Germany in the reorganization and capitalization of the banking system, since 2012 they become similar in structural indicators. The experience of Poland was useful in the period 2010-2014, but in the current conditions banking systems of Ukraine and Poland are beginning to differ significantly. Conclusions. The research results have showed a low level of Ukrainian banking system capitalization, revealed the prospects of applying the capitalization management experience of other countries in the Ukrainian economy. It is necessary additional capitalization of the Ukrainian banking system, because banking risks are significant, requiring increasing bank capital and requires a volume increase of banking activities in general and its role in the formation of Ukraine’s GDP in particular.